Bis{μ-2′-[1-(4-chloro-2-oxidophenyl)ethylidene] thiophene-2-carbohydrazidato}bis-[pyridinezinc(II)] - Ali, Hapipah Mohd; Yamin, B.M.; Yusof, M.S.M.; Mohammad, M. (International Union of Crystallography, 2004)
The title compound, [Zn2(C13H9ClN 2O2S)2(C5H5N) 2], is dimeric via Zn-O bridges with an average Zn-O distance of 2.027 Å. The Zn⋯Zn separation is 3.1003 (5) Å and the geometry of both Zn atoms is square pyramidal. © 2004 International Union of Crystallography Printed in Great Britain - all rights reserved.